The experience of chronic pain among adolescents: suffering and attempt to overcome pain? - Maryam Shaygan; Azita Jaberi (BMC, 2022)
Abstract Background Chronic pain (CP) among adolescents has received less attention than adultsandthere is limited qualitative studies about it in Iran. This study explored the experience of CP among adolescents. Methods This exploratory qualitative study was conducted in April-October 2019. Participants were 14 adolescent students purposively recruited from schools in Shiraz, Iran. Semi-structured interviews were conducted for data collection and data analysis was done through conventional content analysis. Findings Adolescents' experiences of CP came into nine subcategories and three main categories, namely perceived suffering, attempt to overcome pain, and attempt to find sources of support. Conclusion Adolescents with CP experience physical and mental suffering and attempt to manage their pain and its associated suffering through different physical and psychological strategies and using different sources of support such as family, peers, healthcare providers, and school staff.